The use of plants in traditional medicine of the Melanau community in Malaysia - Omar, Salmah; Latip, Malisah (Human Resource Management Academic Research Society, 2022)
Traditional and modern medicine have the same goal of curing diseases and alleviating the suffering experienced by patients in their own concepts and way. Like other traditional communities, the Melanau community also relies on traditional medicine to overcome health-related problems. The entry of elements of modern medicine into the Melanau society does not entirely affect their knowledge and trust in the traditional medical system. This situation occurs because the traditional system is still relevant. It is believed that its ability to heal and cure a disease is incompatible with modern medicine and treatment. The focus of this study was to investigate the use of plants in the traditional medicine of the Melanau community in Sarawak. Primary data was obtained as a result of field studies and library research. Field studies involved the method of interviews with the primary informants, shamans and midwives, and observations of the plants used by them. The information obtained includes how they gain knowledge about the use of plants, the types of plants used, how the plants are used, when they are used, what purpose they are used, and their effects on patients. In general, medicinal plants among the Melanau community have two functions, the first to cure the disease and the second to prevent the disease from developing infections. This study shows that the use of plants in traditional medicine among the Melanau community continues to develop and is practiced until this day. This is because the Melanau community is surrounded by a natural environment that supplies plants in their daily lives. Plants can be found on the banks of rivers, swamps, and forests and planted around the house. The use of natural plants in the environment does not require considerable capital and does not involve a large amount of energy. The continuation of this traditional practice is also influenced by generations' beliefs, knowledge, experience, and skills inherited by the Melanau community. The values, beliefs and heritage of the Melanau community in the use of plants are seen as still relevant and can survive the challenges of today's development and modernization.